Geospatial technologies in school – theoretical concept and practical implementation in K-12 schools. (1st January 2015) - Ditter, R.; Haspel, M.; Jahn, M.; Kollar, I.; Siegmund, A.; Viehrig, K.; Volz, D.; Siegmund, A.
Due to the importance of geospatial technologies (GST) in science, industry and everyday life, they are already included in many K-12 school curricula and the national educational standards for geography in Germany. Studies show, however, that the implementation in school practice as well as the full exploration of GST's educational potential still lags behind. Based on these conditions, one GST programme combines the three pillars research, development of learning environments, and teacher training. All three areas are important not only to further explore the conditions of GST use and especially to evaluate whether and how GST use can contribute to the fostering of geographic competencies, but also to transmit the relevant results to classroom practice by providing teachers with the corresponding materials and training. Examples for each pillar discussed in this paper can give impulses for future (inter)national developments but also highlight some of the present challenges of GST classroom implementation.